A twelve–year retrospective analysis of prevalence and antimicrobial susceptibility patterns of Ureaplasma spp. and Mycoplasma hominis in the province of Lower Silesia in Poland. (January 2018) - Kasprzykowska, Urszula; Sobieszczańska, Beata; Duda-Madej, Anna; Secewicz, Anna; Nowicka, Joanna; Gościniak, Grażyna
Abstract: Objective: Genital mycoplasmas are opportunistic pathogens that have been associated with urogenital infections in humans. Only a few groups of antimicrobials are available for treatment of urogenital tract infections caused by genital mycoplasmas. However, emerging resistance of mycoplasmas to antimicrobial agents has been reported worldwide. The aim of the study was a retrospective analysis of the prevalence and antimicrobial susceptibility patterns of M. hominis and Ureaplasma spp. in patients with urogenital tract infections during a twelve-year period between 2003 and 2015. Study design: Mycoplasma IST2 test was used for the detection, enumeration, identification and antimicrobial susceptibility testing of genital mycoplasmas in 1182 samples from 778 women and 404 men with genitourinary tract infection. Indicative enumeration in the test determines whether the mycoplasma count in the sample is equal or higher than the threshold set at 10 4 colony forming units. Results: A total of 152 (12.8%) samples were found to be positive for genital mycoplasmas. M. hominis was detected only in three samples and Ureaplasma spp. in 141 samples. Both, M. hominis and Ureaplasma spp. were detected in the remaining eight samples. In the analyzed period between 2003 and 2015, a gradually increasing resistance of ureaplasmas to ciprofloxacin and clarithromycin and decreasing resistance to ofloxacin, erythromycin and tetracycline were observed. Pristinamycin, josamycin and doxycycline were most active against Ureaplasma spp. In contrast, fluoroquinolones had the lowest efficacy against Ureaplasma spp. and as many as 116 (82.3%) and 77 (54.6%) of Ureaplasma spp. isolates were resistant to ciprofloxacin and ofloxacin, respectively. M. hominis isolates were uniformly resistant to azithromycin, clarithromycin and erythromycin but susceptible to josamycin, ofloxacin, doxycycline and pristinamycin. One-third of these isolates were resistant to ciprofloxacin and tetracycline. Conclusion: In the study Ureaplasma spp. and M. hominis were detected with relatively low frequency in comparison with other studies however, most of these isolates were resistant to ciprofloxacin indicating the need for better management of ciprofloxacin prescription. Important limitations of Mycoplasma IST2 assay concerning antimicrobial susceptibility testing and divergences between breakpoints in the test and EUCAST guidelines point the need to introduce new methodologies to improve evaluation of resistant strains at our region.